Republicanism in Northeast Asia - Kwak, Chun-hyŏk; Jenco, Leigh K., 1977-; Jenco, Leigh (Political theories in East Asian context ;, 2014)
"As rapid economic development brings increasing uncertainty in East Asia, interest in a new version of republicanism, termed is neo-Roman republicanism, is growing across the region. Conceptualized as liberty as non-domination, this new form of republicanism has inspired not only Western but also East Asian political theorists. However, neo-Roman republican ideas in Northeast Asian countries continue to face serious conceptual and political challenges, which scholarly literature on both republicanism and on East Asian politics has largely failed to confront. This book addresses these challenges by surveying the latest theoretical contributions to the studies of republicanism in Western countries and the latest interpretations of how republicanism, including both communitarian republicanism and neo-Roman republicanism, has been appropriated in countries in East Asia. In particular, it deals with the key question of whether liberty as non-domination can work in non-Western contexts where the fundamental tenets of liberal democracy such as moral individualism and value pluralism, do not predominate. Across three sections, the chapters first provide a conceptual overview of republicanism as a global political theory, they then consider how republicanism has historically been received, resisted, and translated into East Asia, and finally, examine how historically informed possibilities fit with the emergent needs of contemporary Northeast Asian societies"--